Abundancia y distribución de las especies ícticas (Osteichthyes) del río San Francisco-Cosquín, Córdoba, Argentina - Hued,Andrea Cecilia (2001)
It was made the characterization of the San Francisco-Cosquín Mountain River fish community, Córdoba, Argentina. Samples of fish were taken from selected sites from November 1998 to November 1999. Eleven species were recorded, eight of which are first reports for this river. Relative abundance for each species, species richness, diversity and dominance were estimated. Bryconamericus iheringi (Boulenger, 1887) y Jenynsia multidentata (Jenyns, 1842) were the most abundant.